Microsatellite Instability Is Associated With the Presence of Lynch Syndrome Pan-Cancer - Latham, Alicia; Srinivasan, Preethi; Kemel, Yelena; Shia, Jinru; Bandlamudi, Chaitanya; Mandelker, Diana; Middha, Sumit; Hechtman, Jaclyn; Zehir, Ahmet; Dubard-Gault, Marianne; Tran, Christina; Stewart, Carolyn; et al. (Journal of clinical oncology, 2019)
Microsatellite instability (MSI) and/or mismatch repair deficiency (MMR-D) testing has traditionally been performed in patients with colorectal (CRC) and endometrial cancer (EC) to screen for Lynch syndrome (LS)-associated cancer predisposition. The recent success of immunotherapy in high-frequency MSI (MSI-H) and/or MMR-D tumors now supports testing for MSI in all advanced solid tumors. The extent to which LS accounts for MSI-H across heterogeneous tumor types is unknown. Here, we establish the prevalence of LS across solid tumors according to MSI status. MSI status was determined using targeted next-generation sequencing, with tumors classified as MSI-H, MSI-indeterminate, or microsatellite-stable. Matched germline DNA was analyzed for mutations in LS-associated mismatch repair genes ( MLH1, MSH2, MSH6, PMS2, EPCAM). In patients with LS with MSI-H/I tumors, immunohistochemical staining for MMR-D was assessed. Among 15,045 unique patients (more than 50 cancer types), LS was identified in 16.3% (53 of 326), 1.9% (13 of 699), and 0.3% (37 of 14,020) of patients with MSI-H, MSI-indeterminate, and microsatellite-stable tumors, respectively ( P < .001). Among patients with LS with MSI-H/I tumors, 50% (33 of 66) had tumors other than CRC/EC, including urothelial, prostate, pancreas, adrenocortical, small bowel, sarcoma, mesothelioma, melanoma, gastric, and germ cell tumors. In these patients with non-CRC/EC tumors, 45% (15 of 33) did not meet LS genetic testing criteria on the basis of personal/family history. Immunohistochemical staining of LS-positive MSI-H/I tumors demonstrated MMR-D in 98.2% (56 of 57) of available cases. MSI-H/MMR-D is predictive of LS across a much broader tumor spectrum than currently appreciated. Given implications for cancer surveillance and prevention measures in affected families, these data support germline genetic assessment for LS for patients with an MSI-H/MMR-D tumor, regardless of cancer type or family cancer history.